Glial Purinergic Signals and Psychiatric Disorders - Koizumi, Schuichi (Frontiers in Cellular Neuroscience, 2022)
Emotion-related neural networks are regulated in part by the activity of glial cells, and glial dysfunction can be directly related to emotional diseases such as depression. Here, we discuss three different therapeutic strategies involving astrocytes that are effective for treating depression. First, the antidepressant, fluoxetine, acts on astrocytes and increases exocytosis of ATP. This has therapeutic effects via brain-derived neurotrophic factor-dependent mechanisms. Second, electroconvulsive therapy is a well-known treatment for drug-resistant depression. Electroconvulsive therapy releases ATP from astrocytes to induce leukemia inhibitory factors and fibroblast growth factor 2, which leads to antidepressive actions. Finally, sleep deprivation therapy is well-known to cause antidepressive effects. Sleep deprivation also increases release of ATP, whose metabolite, adenosine, has antidepressive effects. These independent treatments share the same mechanism, i.e., ATP release from astrocytes, indicating an essential role of glial purinergic signals in the pathogenesis of depression.